The Concept of Unidirectionally Coupled Nonlinear Circuits via a Memristor - Volos, Ch. K.; Kyprianidis, I. M.; Stouboulos, I. N.; Stavrinides, S. G.; Anagnostopoulos, A. N.; Özer, Mehmet (Polish Acad Sciences Inst Physics, Al Lotnikow 32-46, Pl-02-668 Warsaw, Poland, 2012)
Confirmation of the existence of memristor by researchers at 2008 attracts much interest on this newly found circuit element. This is due to the fact that memristor opens up new functionalities in electronics and it has led to the interpretation of phenomena regarding not only electronics but also biological systems. In this work, we have studied the simulated dynamic behavior of two unidirectionally coupled nonlinear circuits via a memristor. This confirms the transition from chaotic desynchronization to complete chaotic synchronization through a regime of intermittent synchronization between the unidirectionally coupled circuits.